2017
DOI: 10.1007/s11250-017-1496-0
|View full text |Cite
|
Sign up to set email alerts
|

Transrectal ultrasound evaluation in tropical dairy goats: an indispensable tool for the diagnosis of reproductive disorders

Abstract: In Brazil, great milk productivity was achieved after the implementation of a genetic improvement program. However, reproductive efficiency is still far from optimal, possibly due to the high number of undiagnosed disorders that may affect fertility. The aim of this study was to evaluate occurrences of the main reproductive disorders in dairy goats in southeastern Brazil. Data were collected between January 2015 and May 2017 from 23 commercial herds of different breeds, with goats ranging from 8 months to 12 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…Multiple studies have confirmed the close relationship between the gut microbiota and PCOS ( Mammadova et al, 2020 ; Zhao et al, 2020 ). Follicular cysts were also discovered in sheep ( Christman et al, 2000 ; Palmieri et al, 2011 ) and goat ( Medan et al, 2004 ; Maia et al, 2018 ). To our knowledge, there has been no scientific report on the correlation between gut microbiota and follicular cyst in sheep.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have confirmed the close relationship between the gut microbiota and PCOS ( Mammadova et al, 2020 ; Zhao et al, 2020 ). Follicular cysts were also discovered in sheep ( Christman et al, 2000 ; Palmieri et al, 2011 ) and goat ( Medan et al, 2004 ; Maia et al, 2018 ). To our knowledge, there has been no scientific report on the correlation between gut microbiota and follicular cyst in sheep.…”
Section: Discussionmentioning
confidence: 99%
“…Transrectal ultrasonography (Mindray ® DP330-Vet, Shenzhen, China) was performed (according to Maia et al, 2018) ~ 45 days after the end of the reproductive season in all goats. During the exam, the following conditions were evaluated: HD, pregnancy (+) and (-), or with any reproductive disorder other than HD (i.e.…”
Section: Ultrasound Examsmentioning
confidence: 99%
“…However, both may be related to the occurrence of hydrometra (HD) (Duquesnel et al, 1992;Wittek et al, 1997;Batista et al, 2001;Netto et al, 2020). This disease has been associated with a decrease in reproductive efficiency in dairy goats, however, the exact cause of the disease is not elucidated yet (Maia et al, 2018;Menzies 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, obstetric ultrasound has been widely used in small ruminants, administered transcutaneously or transrectally, and with the aim of diagnosing pregnancy, quantifying fetus numbers, sexing, and fetal viability [7,[10][11][12]. Moreover, the use of this tool in goats and sheep has also been highlighted for the diagnosis of pathologies in ovaries and non-pregnant uteri [2,13,14], as well as for the andrological evaluation of testicles and sex glands [8,[14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%